PELAKSANAAN PENGAWASAN CAMAT TENAYAN RAYA KOTA PEKANBARU PADA USAHA PERTAMBANGAN GALIAN C DI KULIM KECAMATAN TENAYAN RAYA - Fitri Ismah; Ahmad Tarmizi Yusa (UIR Press, 2017)
This study aims to determine the sub-district supervision Tenayan Pekanbaru City in overseeing the Pit Mining C. Implementation Supervision Indicators used include direct supervision and indirect supervision is carried out by sub-district Tenayan Pekanbaru City. This type of research is located at the District Office Tenayan Pekanbaru City is a descriptive method with qualitative data analysis. In line with the objectives of the study, the study population is Tenayaran Raya sub-district, District Office Employee Tenayan Kingdom c excavation and mining community. To support the validity and research results, then set the population at the District Office Tenayan Kingdom as many as 6 people and society miners excavated c 8 persons. The sampling technique for the sub-district and District Office Personnel Tenayan puposive Kingdom using sampling techniques and to society c miners excavated using random sampling techniques. Types and techniques of data collection consisted of primary data collected by using questionnaire data and interviews and secondary data collected by observation and documentation techniques that are the source of data and information as well as information from the parties - parties associated with this research. Based on this analysis technique can be concluded that the implementation of sub-district Supervision Pekanbaru City Tenayan In Mining Pit C at Kulim District of Tenayan Kingdom works quite accomplished. The recommendations need to consider is the future of Pekanbaru City District Head Tenayan to conduct intensive monitoring on Mining Excavation C.